2015
DOI: 10.5539/gjhs.v7n4p392
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Breast Cancer Survival Through Knowledge Discovery in Databases

Abstract: The collection of large volumes of medical data has offered an opportunity to develop prediction models for survival by the medical research community. Medical researchers who seek to discover and extract hidden patterns and relationships among large number of variables use knowledge discovery in databases (KDD) to predict the outcome of a disease. The study was conducted to develop predictive models and discover relationships between certain predictor variables and survival in the context of breast cancer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…Using only a very limited set of clinical variables, we demonstrate that our models are capable of predicting meaningful clinical outcomes. Previous studies using the SEER database have used various machine learning methods for diagnosis and prognosis purposes in breast [11][12][13][14][15] and lung cancers, 16,17 but have not applied these techniques to the SEER data on meningiomas. As compared to classical statistical approaches, the value of predictive modeling is the ability to obtain predictions for individual patients rather than group means.…”
Section: Discussionmentioning
confidence: 99%
“…Using only a very limited set of clinical variables, we demonstrate that our models are capable of predicting meaningful clinical outcomes. Previous studies using the SEER database have used various machine learning methods for diagnosis and prognosis purposes in breast [11][12][13][14][15] and lung cancers, 16,17 but have not applied these techniques to the SEER data on meningiomas. As compared to classical statistical approaches, the value of predictive modeling is the ability to obtain predictions for individual patients rather than group means.…”
Section: Discussionmentioning
confidence: 99%
“…SVM is an ML algorithm with a good regularization attribute that is based on the structural risk minimization principle of statistical learning (Xiang et al., 2019). The SVM optimization process maximizes prediction accuracy and reduces over‐fitting of training data (Lotfnezhad, Ahmadi, Roudbari, & Sadoughi, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Among the 31 studies, 9 had a high risk of bias [2,25,27,28,43,44,46,48,50], 17 had a moderate risk of bias [24, 26, 29-35, 39, 41, 42, 45, 47, 49, 51, 52], and 5 ad a low risk of bias [23,[36][37][38]40], as shown in Table 1.…”
Section: Assessment Of the Risk Of Biasmentioning
confidence: 99%
“…For the class imbalance, 24 studies showed class imbalance in the samples of the final model construction [2, 23, 24, 26, 28-37, 40-45, 47-50], and 7 of them dealt with this problem [28,29,34,37,42,47,49]. The methods included undersampling, bagging algorithm, SMOTE, PSO, K-means, KNN, and bagging.…”
Section: Data Preparation and Modelingmentioning
confidence: 99%